2018
DOI: 10.1111/ejss.12747
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the estimation of field capacity and their implications for the bucket type model

Abstract: Summary Field capacity (FC) is crucial for modelling soil–plant–water dynamics with bucket‐type models, supporting prevention of environmental problems (e.g. chemical leaching to deeper layers and groundwater and waste of water resources). As FC measurement in situ is labour intensive, approaches for its estimation have been proposed. However, because they differ conceptually and are based on different assumptions, the response to an application (e.g. crop yield (CY) modelling) can be rather different. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…arbitrarily. A high degree of variability between results from different methods was found (Turek et al, 2019) and this supposedly has an influence over the outcomes of SPQ assessments. Further research concerning the consequences of method choice is required to facilitate study design and the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…arbitrarily. A high degree of variability between results from different methods was found (Turek et al, 2019) and this supposedly has an influence over the outcomes of SPQ assessments. Further research concerning the consequences of method choice is required to facilitate study design and the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight SPQIs used, four are directly linked to field capacity (FC) despite the ongoing discussion which has already led to a range of different determination approaches (e.g. Assouline and Or, 2014;de Jong van Lier, 2017;Turek et al, 2019). Most methods were developed based on extensive databases and with a comprehensible theoretical background, hence they imply comparable reliability and the decision to use a certain method is usually made Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example , Ottoni Filho et al (2016) demonstrated that none of these three suction values in isolation represented in situ FC in their database adequately. Turek et al (2018) analyzed various approaches of indirect determination of FC based on hydrodynamic and hydrostatic criteria, also adopting the suction values of 60, 100 and 330 cm. Their results showed that the FC values in general varied significantly depending on the determination criterion used.…”
Section: Introductionmentioning
confidence: 99%
“…The SWRC is used in soil physics as well as in related areas like hydrology, soil conservation, irrigation and drainage, among others. The SWRC directly links to the soil pore size distribution function, and is used in hydrological studies (Silva et al, 2017), soil physical quality evaluation (Reynolds et al, 2009;Armindo and Wendroth, 2016) as well as in the prediction of field capacity (Turek et al, 2018) and crop water availability (Feddes and Raats, 2004). The understanding of soil water dynamics is important in applications involving infiltration, water redistribution, evaporation, and root water uptake, and helps to promote management that allows an increase in water use efficiency (Prevedello and Armindo, 2015).…”
Section: Introductionmentioning
confidence: 99%